PEMANFAATAN WASTE PENGOLAHAN AIR SEBAGAI AIR UMPAN BOILER PT. NLP - Wahid, Abdul; Hakim, Lukman; Nuriyanto (Prodi Teknik Mesin Universitas Yudharta, 2024)
NLP isafurniture manufacturing company that uses three types of wood, namely mahogany, pine, and teak. Handling and processing sawdust waste is a challenge that needs to be overcome effectively so that the waste can become a product that has added value. The value-dded product in question is souvenir craft. The utilization of coarse sawdust can be mixed with epoxy resin to form composite materials, which can be used as the basic material for souvenir crafts. It is known that the strength of composite materials increases with the increasing composition of the resin in composite materials, and the character of composite materials If the composition of sawdust is higher, the resulting composite material will be opaque and lighter. Then the manufacture of composite materials will use a ratio of 1:1. Regional attributes, cultural elements, innovation in form, design, and ease of application are important factors to consider when designing a product for souvenirs. The collected data is needed to be translated into the interpretation of product requirements to be used in making the Objective Tree and Morphological Diagrams. Evaluation of alternative product designs is carried out by considering the minimum risks.